SISTEM PEMANFAATAN IKAN TUNA DI NUSA TENGGARA (Tuna Utilization System in Nusa Tenggara) - Gigentika, Soraya; Nurani, Tri Wiji; Wisudo, Sugeng Hari; Haluan, John (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2017)
ABSTRACT Competition of tuna utilization in Nusa Tenggara has resulted in the inclining toward irresponsible utilization, which causes various issuess of tuna utilization system in Nusa Tenggara. The objectives of this research are to identify the issues of tuna utilization system in Nusa Tenggara and the root of issues. Analysis data used three steps of Soft System Methodology (SSM), there were understanding of the issues situation, established issues situation, and establish the issues definition. The results showed the issues in tuna utilization system in Nusa Tenggara are illegal installation of FADs; the depleted productivity of tuna fishing unit; inefficient fishing capacity utilization and over-input production input on tuna fishing units, fishermen catch baby tuna (undersized tuna), in optimal quality of landed tuna and conflicts related to FADs utilization. The solution that can be performed for these problems are: 1) Strict and effective law enforcement for illegal FADs and ideal allocated number of FAD’s; 2) determining of optimum allocation number for tuna fishing unit (effort) and the right time for close session; 3) determining the size of the ship which is efficient and determining the optimum amount of effort; 4) Establishing the regulations related to baby tuna fishing, developing the fishing technology which minimizes the catch of baby tuna and controlling the season and the location of the tuna fishing activities; 5) facilitating and training the fishermen and tuna fishing companies or trader for cold-chain handling; and 6) strict and effective law enforcement for fishermen trespassing the fishing area. Keywords: Nusa Tenggara, root definition, tuna utilization system, Soft System Methodology ABSTRAK Persaingan dalam pemanfaatan ikan tuna di Nusa Tenggara mengakibatkan kegiatan pemanfaatan tersebut menjadi cenderung ke arah yang tidak bertanggungjawab, sehingga muncul berbagai permasalahan pada sistem pemanfaatan ikan tuna. Tujuan dari penelitian ini adalah mengidentifikasi permasalahan sistem pemanfaatan ikan tuna di Nusa Tenggara dan upaya yang diperlukan untuk menyelesaikan permasalahan tersebut. Analisis data pada penelitian ini menggunakan tiga tahapan Soft System Methodology (SSM), yaitu memahami situasi permasalahan, menyusun situasi permasalahan, dan menyusun definisi permasalahan. Hasil penelitian menunjukkan bahwa permasalahan pada sistem pemanfaatan ikan tuna di Nusa Tenggara adalah pemasangan rumpon tanpa ijin, penurunan produktivitas unit penangkapan ikan tuna, belum efisiennya pemanfaatan kapasitas dan berlebihnya input produksi pada unit penangkapan ikan tuna, penangkapan baby tuna, belum optimalnya mutu ikan tuna yang didaratkan, serta adanya konflik penggunaan rumpon. Upaya penyelesaian yang dapat dilakukan untuk permasalahan-permasalahan tersebut adalah: 1) penegakkan hukum yang tegas dan efektif untuk rumpon yang tidak berijin serta penentuan alokasi jumlah rumpon yang ideal; 2) penentuan alokasi jumlah effort optimum untuk unit penangkapan ikan tuna dan waktu yang tepat untuk close session; 3) penentuan ukuran kapal yang efisien dan jumlah effort yang optimal; 4) pembuatan regulasi terkait penangkapan baby tuna, pengembangan teknologi penangkapan yang meminimalkan hasil tangkapan baby tuna, serta pengaturan musim dan lokasi penangkapan ikan tuna; 5) penyediaan fasilitas serta pelatihan kepada nelayan dan perusahaan perikanan tuna atau pengumpul ikan tuna untuk penanganan rantai dingin; serta 6) penegakkan hukum yang tegas dan efektif untuk nelayan yang melanggar jalur penangkapan ikan. Kata kunci: Nusa Tenggara, root definition, sistem pemanfaatan ikan tuna, Soft System Methodology